Gadolinium Enhancement May Indicate a Condition at Risk of Developing Necrosis in Marchiafava–Bignami Disease: A Case Report and Literature Review - Wang, Zhiqin; Wang, Jianfeng; Yi, Fang; Zhou, Lin; Zhou, Yafang (Frontiers in Human Neuroscience, 2019)
Marchiafava–Bignami disease (MBD) is a rare condition characterized by demyelination, necrosis and atrophy of the corpus callosum (CC), and mainly associated with alcoholism. MBD may present with various clinical manifestations. Brain magnetic resonance imaging (MRI) scan is important in prompt diagnosis and treatment of MBD. Here we reported a case of MBD and reviewed literature about the usage of gadolinium-enhanced MRI in MBD. Gadolinium enhancement may indicate a condition at risk of developing necrosis. We therefore recommend a contrast-enhanced MRI study in severe alcoholics with suspected diagnosis of MBD.